Kepribadian Indonesia Unggul Untuk Mencegah Cyber Bully Akibat Kampanye Politik Ditinjau Dari UU ITE - Nurlaila Suci Rahayu Rais; M.Maik Jovial Dien; Yayu Hizza Anisa (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2015)
The rapid technological advances in mass communication makes social media is also evolved and this becomes a concern will bring a negative impact on the social life of the Indonesian society. Widespread acts of violence committed in cyberspace (cyber bullying) during the campaign leading up to the election being held to be one proof of such concerns. This research is qualitative descriptive research method uses interview techniques and the library research. The author also observed in the field by examining the development of the implementation of Pancasila personality structure that will be used as a reference in solving the problems of the subject matter. The results show that cyber bullying is a crime committed in online social media such as to harass, threaten, embarrass, humiliate, isolate socially, or damage the reputation of others for the sake of the offender. This cyber bullying can be subject to legal sanctions. UU ITE set in Article 27 Paragraph (3), Article 28, Paragraph (1) and Article 28, Paragraph (2). The impact of cyber bullying is a victim that potentially suffering from a psychiatric disease such as a psychopath, not confident, or anti-social. To prevent cyber bullying necessity embodied the Excellence of Indonesian Personality that characterizes the Indonesian nation of true moral Pancasilaist with the practice of sila-sila Pancasila in the life of society, nation and State.